The Influence of The Ease of Information and The Ease of Transaction on Online Purchasing Decisions at Bika Ambon Rika Store on Sekip, Medan in The Digital Era - Lee, Clara; Bambang Sutejo (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2023)
Bika Ambon is one of the specialty cakes from Medan, North Sumatra. One of the well-known Bika Ambon shops in Medan is Toko Bika Ambon Rika. Toko Bika Ambon Rika was previously only sold offline. Now, due to the development of technology and accessibility in the digitalization era, Toko Bika Ambon Rika has started selling online in order to maintain its business in this digitalization era. Thus, this study was conducted to analyse the effect of ease of information and ease of transactions on online purchasing decisions at Toko Bika Ambon Rika, Medan, in this digital era. The population in this study were consumers of Toko Bika Ambon Rika who had made at least one or more online purchases within the past year. The number of samples in this study was determined by the method of Hair et al. (1998), so the minimum sample size that researchers must obtain in this study is 165 respondents. From the results of the coefficient of determination, it can be concluded that the effect of the Ease of Information and Ease of Transaction variables simultaneously on Y is 35.7%, while the remaining 64.3% is influenced by other factors.